Növényi adalékanyagok hatásának tanulmányozása liszt sütési tulajdonságaira és pékáruk minőségi mutatóira - Alkhamova Guzel (Élelmiszervizsgálati közlemények, 2020)
We studied functional properties of whole fenugreek seeds Trigonella foenum graecum L., black cumin seeds Nigella sativa, stevioside (steviosides) and their effect on organoleptic, physical, and chemical properties of bakery products made from wheat flour. Due to the wide range of useful components, fenugreek, black cumin, and stevioside possess hypoglycemic, antimicrobial, anti-inflammatory, anabolic, anticoagulant, and antioxidant properties. The aim of the work was to develop functional bakery products and to study quality indicators of white bread made from wheat flour with partial replacement of wheat flour with fenugreek seeds, black cumin seed flour, and replacement of sugar with stevioside. The following samples were under study: the control sample, samples with 2 and 2.5% fenugreek seeds, 1 and 1.5% black cumin seed flour in relation to the weight of wheat flour, as well as with the complete replacement of granulated sugar with stevioside. © 2020, Wessling International Research and Educational Centre Nonprofit Beneficial Ltd.. All rights reserved.